Gra jako implikacja koordynacyjnych uwarunkowañ - Machnaz, W. (Human Movement, 2001)
The term game, although it is an expression used very frequently in everyday life, is often defined in a variety of ways. This phenomenon is due to the fact that it functions in various domains of human activity. The notion of game is particularly employed in the sciences of physical culture. Sports game is a process involving all methods and activities which aim at achieving higher effective result by its participants. In other words, it is a process in which certain "abstract entities" are produced in order to allow comparison between the competing parties. The fact of using the expression "abstract entity" is the evidence that, if we take into account a wide understanding of the term "product", its various forms may, and will occur as effective values. Therefore, a sports game is an environmental attempt or a test for domination, pursuing ambition and skills for producing "entities" which are recognised by physical culture as important. This type of competition stems from the fact that, in the course of direct confrontation, one subject aims at achieving this value while the other from the opposite position tries to stop its opponent. It becomes a rule to divert roles, that is to divert the cause and effect sequence. The final result of the game is the resultant of the competing participants' attempts as part of these activities. Thus, game is characterised by the unique rhythm measured by the mobile mechanism of efficacy in competition. The axis and the essence of a sports game is the achieved numerical result while in the background there are hopes and emotions. In ball games, the ball is a tool by means of which the players achieve their goals. Ball games are perceived as dynamic structures characterised by countless interactions between the participating parties. That is to say that, through instrumental ways of behaving, the players influence one another. As it can be seen, this kind of competition is directed towards correlation activities. It is therefore absolutely essential, inherent in the logic of the competition, that the opponent be present. Ball games are dynamic structures not only in the sense that within the enclosed time period there is a combination of occurrences and results, but also since they are systems in motion. The players in constant motion change the margins of ability and inability to influence the course of the game, which means that they all are in temporary situations. New situations enforce subsequent decisions as to the further activities and decisions must be made relatively quickly. What is more, each subject has at its disposal a collection of alternatives and chooses from among them such an activity which enables successful realisation of the task. The necessity to choose a way and, in fact, limitless possibilities of acting depict skills as well as preferences of the performers. To achieve success, it is necessary to be talented. It is little known what underlies aptitude for ball games. According to authoritative sources, we can conclude that it is a collection of features at somebody's disposal [19], a complex of determinants of usefulness for sport [9, 10], hypothetical component which creates a base or supports the process of achieving sports tasks [14]. It is generally accepted that aptitude for sport has complex and multiple-layer character, although there is a tendency to simplify the reality and seek for one factor explaining a wide range of this phenomenon. Therefore, which factor should be associated with this type of activity? In our opinion, the term "co-ordination" is acceptable. It is hard to imagine the existence of a ball game where this factor could be excluded. In reference to games, this term has two aspects as it is used to determine various and specific processes. In the first meaning, it refers to the player (subject) and is identified with the individualistic set of motor skills (features) or even more widely as a set of individualistic features. In the second meaning (objective), it refers to the set of effects arising from the functioning of organised systems such as sport teams.